2015
DOI: 10.1038/srep15879
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of bombesin-induced tonic contraction of the porcine lower esophageal sphincter

Abstract: Gastroesophageal reflux disease (GERD) is a disorder that is related to an incompetent lower esophageal sphincter (LES). Previous studies showed that bombesin could increase LES pressure in humans and opossums. The aim of the present study was to characterize the effects of bombesin on porcine LES contraction. We used the selective agonists, neuromedin B (NMB), gastrin-releasing peptide (GRP), and [D-Tyr6,Apa-4Cl11,Phe13,Nle14]bombesin-(6-14) (DTACPN-BN), as well as receptor antagonists of bombesin receptor su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 28 publications
(35 reference statements)
0
10
0
Order By: Relevance
“…The porcine LES, which has similar structure to the human LES, was divided into clasp with LC and sling with GC muscle strips according to previously published procedures with minor modifications (Farré et al, 2007; Tsai et al, 2015, 2018). The porcine LES is often used as an animal model system to study esophageal motility and GERD in humans (Korn et al, 1997; Schopf et al, 1997).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The porcine LES, which has similar structure to the human LES, was divided into clasp with LC and sling with GC muscle strips according to previously published procedures with minor modifications (Farré et al, 2007; Tsai et al, 2015, 2018). The porcine LES is often used as an animal model system to study esophageal motility and GERD in humans (Korn et al, 1997; Schopf et al, 1997).…”
Section: Methodsmentioning
confidence: 99%
“…Immunostaining with anti-FFA1 (polyclonal, GeneTex, CA, United States) and anti-FFA4 (polyclonal, GeneTex, CA, United States) antibodies were executed on the fully automated Bond-Max system (Leica Microsystems, Nussloch, Germany) according to previously described procedures with minor modifications (Tsai et al, 2015, 2018). Slides carrying tissue sections of porcine sling and clasp muscles, cut from paraffin-embedded, formalin-fixed sections, were dried for 30 min at 60°C.…”
Section: Methodsmentioning
confidence: 99%
“…NMB exerts several biological functions by binding NMBR, such as stimulating smooth muscle, mediating stress and fear reactions, regulating feeding, regulating temperature, energy balance, regulating endocrine and/ or exocrine secretions and promoting cell growth (Ohki-Hamazaki 2000, Jensen et al 2008). In addition, NMB can stimulate the hypothalamic-pituitary-gonadal (HPG) axis in male rats, which indicates that NMB can also regulate reproduction (Boughton et al 2013); however, little is known about the physiological functions of NMB in pigs, except that it can contract the porcine lower esophageal sphincter (Tsai et al 2015). We had previously found that NMB and NMBR mRNAs are expressed in pig testes and that they exhibit developmental changes in the gonadal axis of boars (Ma et al 2016); therefore, we speculated that the NMB/NMBR system might have an impact on the reproductive function of boars.…”
Section: Discussionmentioning
confidence: 99%
“…As explained previously, bombesin mediates its functions through specific receptors. Additionally, bombesin and their receptors are widely distributed in the periphery and CNS, and are associated with various functions like food intake, pain, stress, and fear responses [ 23 ]. Henceforth, it will be meaningful for scientists to study the physiological and pathological aspects of bombesin relationships with receptors in amphibians.…”
Section: Discussionmentioning
confidence: 99%